Al-Quran dan Epistemologi Pembebasan - Muhammad Saifullah (MAGHZA, 2018)
This article tries to explore Jamal's interpretation of á¸¥ikmah in the Quran. Beside the discourse of á¸¥ikmah still being polemic, Jamalâ€™s decision to lay á¸¥ikmah into fundamental place upon his broad thought is an obvious factor why they were chosen herein. One could catch the later through how Jamal in his interpretation had parallelized á¸¥ikmah with Syafiiâ€™s particular word, qiyÄs. Jamal criticized Syafiiâ€™s interpretation in relation to á¸¥ikmah which state that á¸¥ikmah was not anything except sunnah. On another hand, he also put his construction of á¸¥ikmah into what he called as new Islamic systematic knowledge, al-mandhumah al-jadidah li maâ€™rifat al-Islamiyyah. He regretted fiqh which had made many Moslems being oppressed either in thought or physic and subsequently proposed á¸¥ikmah as the change of fiqh as the third source of new Islamic systematic knowledge. In time, there are two critical points concerning Jamalâ€™s interpretation and the oppressed, those are Jamalâ€™s status as a labor activist and Quranic revolution as the giant project. The article is, thus, plagued to analyze what actually Jamal desired through his interpretation regarding the new source, the Quranic revolution, and labor activist. The frame of critical discourse analysis of Van Dijk felt suitable to be employed herein.